Limited evolution of the yellow fever virus 17d in a mouse infection model - Dieudonné Buh Kum; Niraj Mishra; Bram Vrancken; Hendrik Jan Thibaut; Annelies Wilder-Smith; Philippe Lemey; Johan Neyts; Kai Dallmeier (Emerging Microbes and Infections)
By infecting mice with the yellow fever virus vaccine strain 17D (YFV-17D; Stamaril®), the dose dependence and evolutionary consequences of neurotropic yellow fever infection was assessed. Highly susceptible AG129 mice were used to allow for a maximal/unlimited expansion of the viral populations. Infected mice uniformly developed neurotropic disease; the virus was isolated from their brains, plaque purified and sequenced. Viral RNA populations were overall rather homogenous [Shannon entropies 0−0.15]. The remaining, yet limited intra-host population diversity (0−11 nucleotide exchanges per genome) appeared to be a consequence of pre-existing clonal heterogeneities (quasispecies) of Stamaril®. In parallel, mice were infected with a molecular clone of YFV-17D which was in vivo launched from a plasmid. Such plasmid-launched YFV-17D had a further reduced and almost clonal evolution. The limited intra-host evolution during unrestricted expansion in a highly susceptible host is relevant for vaccine and drug development against flaviviruses in general. Firstly, a propensity for limited evolution even upon infection with a (very) low inoculum suggests that fractional dosing as implemented in current YF-outbreak control may pose only a limited risk of reversion to pathogenic vaccine-derived virus variants. Secondly, it also largely lowers the chance of antigenic drift and development of resistance to antivirals.